Recent Trends in Information and Communication Technology : Proceedings of the 2nd International Conference of Reliable Information and Communication Technology (IRICT 2017) - International Conference of Reliable Information and Communication Technology (2nd : Johor, Malaysia); Faisal Saeed, editor 616310; Nadhmi Gazem, editor 616309; Srikanta Patnaik editor; Ali Saleh Saed Balaid, 1972-, editor 604857; Fathey Mohammed, editor 618610; SpringerLink (Online service) (Cham, Switzerland : Springer, 2018)
This book presents 94 papers from the 2nd International Conference of Reliable Information and Communication Technology 2017 (IRICT 2017), held in Johor, Malaysia, on April 23-24, 2017. Focusing on the latest ICT innovations for data engineering, the book presents several hot research topics, including advances in big data analysis techniques and applications; mobile networks; applications and usability; reliable communication systems; advances in computer vision, artificial intelligence and soft computing; reliable health informatics and cloud computing environments, e-learning acceptance models, recent trends in knowledge management and software engineering; security issues in the cyber world; as well as society and information technology.